A feasible schedule for parallel assembly tasks in flexible manufacturing systems - Majdzik, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
The paper concerns the design of a framework for implementing fault-tolerant control of hybrid assembly systems that connect human operators and fully automated technical systems. The main difficulty in such systems is related to delays that result from objective factors influencing human operators` work, e.g., fatigue, experience, etc. As the battery assembly system can be considered a firm real-time one, these delays are treated as faults.
Keywords: parallel system; synchronization; scheduling; discrete event systems; wireless equipment